2016
DOI: 10.1021/acs.jpcc.6b02263
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Fission in Quinoidal Oligothiophenes

Abstract: The electronic properties of quinoidal oligithiophenes make them interesting for applications in semiconductor technology. Because of their very large singlet− triplet splitting, they are promising candidates for singlet fission (SF), a process in which an initially excited singlet state is converted into two triplet excitons. Thus, the efficiency of solar cells could be increased to overcome the ShockleyQueisser limit. Here, we investigate the ability of a quinoidal bithiophene to undergo SF in solution. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…[132][133][134][135] For their modeling, the use of a multiplicity independent Hamiltonian is mandatory in a DFT/MRCI treatment. 88,[136][137][138][139] Contrary to monomeric nucleobases, strange results are obtained for a hydrogen-bonded adenine-thymine Watson-Crick base pair if the original DFT/MRCI Hamiltonian is employed. In these calculations, the first excited singlet state corresponds to a double excitation with ππ 0 !…”
Section: Critical Casesmentioning
confidence: 99%
See 3 more Smart Citations
“…[132][133][134][135] For their modeling, the use of a multiplicity independent Hamiltonian is mandatory in a DFT/MRCI treatment. 88,[136][137][138][139] Contrary to monomeric nucleobases, strange results are obtained for a hydrogen-bonded adenine-thymine Watson-Crick base pair if the original DFT/MRCI Hamiltonian is employed. In these calculations, the first excited singlet state corresponds to a double excitation with ππ 0 !…”
Section: Critical Casesmentioning
confidence: 99%
“…In the case of π-stacked dimers, it may be necessary to add a semiempirical dispersion correction, such as Grimme's D3 correction, 140,141 to obtain a properly bound ground state. 138 The dispersion corrections mainly affect the molecular geometry. For a given nuclear arrangement, the D3 corrections have no impact on the MOs and the DFT/MRCI Hamiltonian and hence on the electronic spectrum.…”
Section: Critical Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical studies have been performed in order to find new SF molecules that fulfill the critical energetic criteria E(S 1 ) > 2E(T 1 ), [12,13] and also to understand its underlying mechanism (a detailed review can be found in Ref. [14]) but many questions of how this process actually occurs are still active areas of research; these include the role of the vibrational modes [15][16][17][18][19] and charge transfer (CT) states [20,21] in the SF process.…”
Section: Introductionmentioning
confidence: 99%